The Impact of Biopreneurship Project-Based Science Learning on Students' Entrepreneurial Creativity - Artayasa, I Putu; Rosyidi, M. Akhyar; M. M. Awang Kechik; Yustiqvar, Muhammad (Jurnal Pendidikan IPA Indonesia, 2024)
Developing students' entrepreneurial creativity is essential to taking advantage of opportunities in new economic areas. The integration of biopreneurship in project-based learning offers an exciting solution. The impact of that learning model is measured by comparing pre- and post-intervention capabilities between groups that received and did not receive treatment. This study aims to determine the impact of biopreneurship project-based science learning on students' entrepreneurial creativity in the Mandalika Special Economic Zone. This research is quasi-experimental type, with a nonequivalent pretest-posttest control group design. The population of this study was junior high school students in the Mandalika Special Economic Zone. One hundred ninth-grade students from two schools were selected as research samples using a purposive technique. Students from each school were grouped into experimental and control classes. The experimental class applied biopreneurship project-based learning, while the control class implemented conventional science learning using lecture and discussion methods. Data was collected using entrepreneurial creativity tests, interviews, and questionnaires. Data analysis consisted of prerequisite tests (normality and homogeneity tests) and research hypothesis tests (t-test and Mann-Whitney test). Experimental class students had a significantly higher average entrepreneurial creativity than the control class students. This study concludes that biopreneurship project-based science learning significantly impacts students' entrepreneurial creativity.